Quantifying Key Mechanisms That Contribute to the Deviation of the Tropical Warming Profile From a Moist Adiabat. Issue 20 (15th October 2020) - Miyawaki, Osamu; Tan, Zhihong; Shaw, Tiffany A.; Jansen, Malte F.
Abstract: Climate models project tropical warming is amplified aloft relative to the surface in response to increased CO2 . Here we show moist adiabatic adjustment overpredicts the multimodel mean 300 hPa temperature response by 16.6–25.3% across the CMIP5 model hierarchy. We show three mechanisms influence overprediction: climatological large‐scale circulation, direct effect of increased CO2, and convective entrainment. Accounting for the presence of a climatological large‐scale circulation and the direct effect of CO2 reduces the CMIP5 multimodel mean overprediction by 0.7–7.2% and 2.8–3.9%, respectively, but does not eliminate it. To quantify the influence of entrainment, we vary the Tokioka parameter in aquaplanet simulations. When entrainment is decreased by decreasing the Tokioka parameter from 0.1 to 0, overprediction decreases by 9.6% and 10.4% with and without a large‐scale circulation, respectively. The sensitivity of overprediction to climatological entrainment rate in the aquaplanet mostly follows the predictions of zero‐buoyancy bulk‐plume and spectral‐plume models. Plain Language Summary: Climate models project tropical warming is amplified in the upper troposphere in response to increased CO2 . This is expected based on a simple model that considers the latent heat released from condensation of water vapor in a rising plume (moist adiabat). The vertical profile of warming has important implications for the strength of convective storms, the subtropical climate, and the climate sensitivity. Here we compare the moist adiabatic prediction of the response to increased CO2 across a hierarchy of climate models. We find that the moist adiabatic temperature profile overpredicts the tropical warming aloft in response to increased CO2 . We quantify the influence of three mechanisms that are missing in the simple model of a rising plume: (1) the presence of a climatological large‐scale circulation, (2) the radiative effect of increased CO2, and (3) the mixing of dry environmental air into the rising plume. Accounting for the first two mechanisms reduces the overprediction but does not eliminate it. In idealized aquaplanet simulations, we find that weaker mixing leads to smaller overprediction, in agreement with the expectation that the mixing of dry air dilutes rising plumes and decreases the latent heat released from condensation. Key Points: Moist adiabatic adjustment overpredicts the tropical upper tropospheric temperature response to increased CO2 across CMIP5 climate models The overprediction is nonzero after accounting for the presence of a climatological large‐scale circulation and the direct effect of CO2 GFDL AM2.1 aquaplanet simulations show that overprediction decreases with decreasing climatological entrainment rate